IDENTIFIKASI SENYAWA BIOAKTIF PADA KULIT IKAN SEMBILANG (Paraplotosus albilabris) DAN POTENSINYA SEBAGAI ANTIBAKTERI - Yulia Oktavia; Made Suhandana; Alen Fri Jacky Pasaribu (Marinade, 2023)
Eel tail catfish is one of the aquatic organisms that contains bioactive compounds. These bioactive compounds have the potential to be developed into anticancer, antimicrobial, and antioxidant properties. The aim of this study was to extract bioactive compounds and measure antibacterial activity. Maceration using three different organic solvents (ethanol, n-hexane, and methanol) was used to remove the bioactive compounds on fish skin. Analysis indicators carried out were identification of bioactive compound, toxicity assay (Brine Sirmp Lethaly Test), and antibacterial activity (agar diffusion). The results of this study showed that ethanol and methanol were able to remove more bioactive compounds than n-hexane, the LC50 of fish skin extract from eel tail catfish (ethanol, methanol, and n-hexane) which was 451.42 ppm; 33853.22 ppm; 29513.84 ppm. The extraction with ethanol had the highest inhibition zone 93 mm for Staphylococcus aureus and 74 mm for Escherichia coli bacteria. It is suspected that the bioactive is classified as a polar bioactive compound.